Effect of potassium fertilization on the postharvest quality of 'Fuji' apples - Hunsche, Maurício; Brackmann, Auri; Ernani, Paulo Roberto (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this study was to evaluate the effects of soil K fertilization on fruit mineral composition, quality and storability of 'Fuji' apples. Fruits from a long-term trial that evaluated apple response to annual soil applications of K2O for nine years were harvested in the 1999/2000 growing season and stored in controlled atmosphere (CA) of 1 kPa O2/ < 0.3 kPa CO2 or 1 kPa O2/2.0 kPa CO2. Apples were analyzed for quality and ripening parameters at harvest, after eight months of CA storage, and after seven days at 20ºC after harvest and after CA storage. The increase on soil K fertilization raised fruit mass, diameter, titratable acidity, red color, and K contents while decreased flesh firmness. There was a significant interaction between K fertilization and storage atmospheres only for internal breakdown: when fruits were stored under 1 kPa O2/ < 0.3 kPa CO2 no differences were determined between treatments. However, storing apples under 1 kPa O2/2.0 kPa CO2 resulted in higher breakdown in fruits with lower K concentrations. Fruit weight losses during storage, ground color and rot incidence were not affected by soil K fertilization in the previous nine years.